O que as mobilizações de rua contra demarcações de terras indígenas de 2013 tem a nos dizer? - Rauber, Marcelo Artur (2023)
In addition to the large urban demonstrations that took place in Brazil in 2013, there were also several demonstrations in small and medium-sized municipalities, but for a specific agenda: the Indigenous lands. The aim of this article is to analyze the demonstrations against the regularization of Indigenous lands, identify the main social groups involved and their forms of action. The results show that the Parliamentary Front of Agriculture, agricultural employers' organizations and family farming unions were the protagonists of these actions, carried out mainly in the center-south region of Brazil.